2014
DOI: 10.1136/annrheumdis-2014-eular.1484
|View full text |Cite
|
Sign up to set email alerts
|

FRI0461 Subclinical Ovarian Dysfunction in Takayasu Arteritis Patients

Abstract: Background Takayasu arteritis (TA) is a rare idiopathic systemic chronic vasculitis that involves large arteries. This disease occurs mainly in female gender during the reproductive age and ovarian reserve and future fertility are major topic of interest. Aging, surgery and hypothalamic-pituitary-gonad axis dysfunction have been found to influence the quantity and quality of primordial follicles in ovaries and, ultimately, the ovarian reserve. Other conditions such as autoimmune oophoritis and immunosuppressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a small case‐control study, reduced ovarian reserve was noted in patients with TA as measured by anti‐Müllerian hormone 22 . In that study, they also found that diminished follicular reserve was not related to therapy of TA.…”
Section: Implications Of Takayasu Arteritis For Fertilitymentioning
confidence: 90%
“…In a small case‐control study, reduced ovarian reserve was noted in patients with TA as measured by anti‐Müllerian hormone 22 . In that study, they also found that diminished follicular reserve was not related to therapy of TA.…”
Section: Implications Of Takayasu Arteritis For Fertilitymentioning
confidence: 90%